Pengaruh Motivasi Belajar terhadap Hasil Belajar Mahasiswa dalam Mata Kuliah Konsep Dasar IPA I di STAI Al-Munawwarah - Suheria Suheria; Mutmainna Mutmainna (Jurnal Kajian Pendidikan IPA, 2026)
Student success in the learning process is strongly shaped by learning motivation, regarded as a crucial internal determinant. This study was conducted to reveal the extent to which learning motivation affects student learning outcomes in the Basic Concepts of Science I course at STAI Al-Munawwarah Tolitoli. An ex post facto design with a quantitative approach was employed. The population consisted of 102 students of the PGMI Study Program at STAI Al-Munawwarah Tolitoli, from whom 23 third-semester students were purposively selected as the sample. Learning motivation scores were collected via a questionnaire, while learning outcomes were measured using course grades. Data analysis techniques included classical assumption tests covering normality, linearity, heteroscedasticity, and autocorrelation. Hypothesis testing was subsequently carried out using simple linear regression in IBM SPSS Version 22. The results showed that the data met the assumptions of normality (Sig.). value of 0.083 > 0.05, linearity with a Sig. value of 0.002 < 0.05, heteroscedasticity with a point distribution forming no particular pattern, and autocorrelation with a Sig. value of 0.061 > 0.05. Simple linear regression analysis produced the equation Y = 14.825 + 1.898X with a significance value of 0.002 < 0.05, indicating that learning motivation has a positive and significant effect on student learning outcomes. The coefficient of determination (R Square) of 0.217 indicates that learning motivation accounts for 21.7% of learning outcomes, while the remaining 78.3% is explained by other factors beyond this study. Thus, learning motivation is an important factor that must be continuously strengthened to support student learning in the Basic Concepts of Science I course.Keywords: learning motivation, learning outcomes, science education, students